Literature Reading and Writing Proficiency in Class II Elementary School Students Through Online Learning (International Journal of Scientific Research and Management (IJSRM), 2021)
This study aims to describe the development of reading and writing literacy skills for second-grade students of SD Islam Al-Azhar 13 Rawamangun, East Jakarta. This research is a case study research that utilizes observation, interviews, document studies, and tests as data collection techniques. The development of reading and writing literacy for elementary school students in grade II begins with the emergency curriculum review process, syllabus and lesson plans design, learning implementation, and ends with an evaluation. The results of reading learning activities which consist of three activities of reading aloud reading texts, reading comprehension, and reading poetry texts indicate a very good level of students’ reading skills. Writing lessons focused on writing simple poems according to pictures and writing simple texts according to pictures using punctuation marks and capital letters also showed excellent student skills. Thus, it is concluded that the online learning conducted by Al-Azhar Islamic Elementary School 13 Rawamangun to improve students’ reading and writing literacy skills has been effective with various supporting factors.